Floral organogenesis and vasculature in Mayacaceae, an enigmatic family of Poales - Oriani, Aline [UNESP]; Scatena, Vera L. [UNESP] (Springer Nature, 2019)
Mayacaceae are a small and monogeneric aquatic family including 4–6 species and with an unstable phylogenetic position within Poales. Therefore, the floral development and vasculature were studied in Mayaca fluviatilis and Mayaca sellowiana to better understand interfamilial relationships. In both species, the floral vascular system is organized in six central complexes from which the traces of all floral parts diverge. Both sepals and petals receive three traces, but in the sepals the median and lateral traces do not originate from the same vascular complex, whereas in the petals the median and lateral traces originate from the same complex. Both, ventral and dorsal carpellary traces, vascularize the ovary wall, ascending to the stigma. The sepals are the first organs to be initiated and have a rapid growth. Such structures exhibit glandular trichomes on their margins and remain united, protecting the inner whorls. After sepal development, the petals and the stamens of the outer whorl are initiated, followed by the gynoecium, which appears as an annular primordium. The petals have a markedly delay in development. In M. fluviatilis, the anthers may dehisce before anthesis and self-pollination occurs in the bud. The reduction (loss) of the inner stamen whorl and gynoecium development from an annular primordium link Mayacaceae to the cyperids (Poales). A high similarity in respect to floral vasculature was observed between Mayacaceae and Commelinaceae (Commelinales).
Keywords: Cyperids; Floral anatomy; Gynoecium; Mayaca; Ontogeny; Xyrids